Pluralitas Dalam Teori Perencanaan - Priyani, Rina (Center for Research and Community Services ITB, 2007)
Pluralism is nothing new but plurality approach in planning theory is a recent reaction to the failture of rational comprehensive planning. Planning itself is considered to be “a good planning” if it could accommodate the plurality. The idea of plurality c an be explored in diversity and difference concepts as coined by Sandercock. This article aims to discuss plurality in planning theory using the phenomenon of urban heritage as one of multicultural city‟s assets. Opportunity and limitation indeveloping the concepts are discussed to emphasize its contribution to planning theory and practice.